2020
DOI: 10.1590/0102-311x00245818
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption and depression among Brazilian adults: results from the Brazilian National Health Survey, 2013

Abstract: Our study aimed to evaluate the association between food consumption and depression. We used data from the Brazilian National Health Survey; a cross-sectional study carried out in 2013 among 46,785 Brazilian adults. The exposures were regular consumption (≥ 5 times/week) of the markers of healthy (beans, vegetables, fruits, and natural fruit juices) and unhealthy food (sugar sweetened beverages; sweets and the substitution of lunch or dinner for snacks); and a nutritional score elaborated by combining the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(33 reference statements)
0
8
0
1
Order By: Relevance
“…Considering the COVID-19 context and the higher vulnerability of people with mental disorders for psychological distress, a possible explanation can be through the association between higher perceived stress and food choices, in which people with higher stress tend to increase the consumption of sugary foods 19,20 . The similar increases in the low consumption of fruits or vegetables among participants with and without a previous diagnosis of depression reflect the already low prevalence of recommended consumption of fruit and vegetables before the pandemic 18 . A previous study also found that the consumption of fruits and vegetables was not associated with elevated depressive symptoms using the Brazilian National Health Survey 18 .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Considering the COVID-19 context and the higher vulnerability of people with mental disorders for psychological distress, a possible explanation can be through the association between higher perceived stress and food choices, in which people with higher stress tend to increase the consumption of sugary foods 19,20 . The similar increases in the low consumption of fruits or vegetables among participants with and without a previous diagnosis of depression reflect the already low prevalence of recommended consumption of fruit and vegetables before the pandemic 18 . A previous study also found that the consumption of fruits and vegetables was not associated with elevated depressive symptoms using the Brazilian National Health Survey 18 .…”
Section: Discussionmentioning
confidence: 60%
“…The similar increases in the low consumption of fruits or vegetables among participants with and without a previous diagnosis of depression reflect the already low prevalence of recommended consumption of fruit and vegetables before the pandemic 18 . A previous study also found that the consumption of fruits and vegetables was not associated with elevated depressive symptoms using the Brazilian National Health Survey 18 . Contrary to our initial hypotheses that people with previous diagnosis of depression would present higher rates of physical inactivity and high TV-viewing incidence during the COVID-19 pandemic quarantine, we found that the incidence of both indicators was similar among participants with and without depression.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Pesquisas comprovam, ainda, que pessoas com depressão são mais propensas a consumir alimentos ricos em açúcar, sendo um fato alarmante quando se relaciona essa condição com o estresse Brazilian Journal of Health Review, Curitiba, v.4, n.2, p. 8464-8477 mar./apr. 2021 psicológico do COVID-19 (RENZO et al, 2020;SOUSA et al, 2020;WERNECK et al, 2020).…”
Section: Metodologiaunclassified
“…Further, we recently reported increased risk of depressive symptoms among workers who frequently consumed soft drink (6) . Regarding sweet foods, eight studies have examined the association with depressive symptoms or perceived stress, and all have observed an increased prevalence or incidence of depressive symptoms (2,5,(7)(8)(9)(10)(11) or perceived stress (12) . Of these studies, only two were prospective (2,5) and no study was conducted among Asian populations.…”
Section: Introductionmentioning
confidence: 99%